O impacto da Política Nacional Antidrogas na lotação dos presídios capixabas entre 2011 a 2016 - Ricas, Eugênio Coutinho (2018)
This research followed the line legal aspects in the public sector and deals with the subject of prison population and is guided by the following research problem: to what extent is Law 11,343 / 2006 related to the increase in the prison population? The objective of this study is to understand the relationship between the national anti-drug policy, materialized by the advent of Law 11,343 / 2006, and the increase in the prison population in the prisons of Espírito Santo from 2011 to 2016. Research indicates the growth of the prison population in Brazil from 2006, with the entry of this law that became known as "anti-drug law". Espírito Santo accompanies this growth and places itself in sixth place in the country in proportional amount of prisoners. This research, therefore, has relevance and justification for its potential to contribute in greater depth to the understanding of this reality, to enrich debates and, consequently, to generate propositions that result in solutions to the problem, especially in the legal field. This is a documentary research that covers a sample of 150 sentences issued by judges from the counties of Greater Vitória, whose data are analyzed by the technique of content analysis. The results indicate that the anti-drug law has significantly impacted the prison population in Espírito Santo from an estimated five thousand prisoners in 2006 to more than 20,000 in 2017, a fourfold increase. Detailed analyzes of these prisons show that this increase is directly related to the edition of the law, among which we can highlight: the difference between the percentage growth of the total number of prisoners from 2010 to 2017 (approximately 80%) and the growth of prisoners by trafficking in the same period (approximately 120%); 84% of men and 90% of women did not carry weapons or ammunition at the time of arrest; the relationship between the penalty and drug variables apprehended indicates the existence of subjectivism in the application of law 11343/2006, associated with social factors such as race and origin of residence, mainly. The result of these analyzes can serve as a basis for a possible legislative change, which is the main product of the present research.